Layout and Optimization of Urban Stormwater Management Measure: A Review - LIU Jie; SHANG Yuchang; ZHANG Xiang; GUI Haijiao (Renmin Zhujiang)
Urban stormwater management is an international research hotspot and frontier, and it is also a major demand for urban green development in China. In this context, China vigorously promotes the construction of sponge cities but still faces many challenges, among which the spatial layout optimization of stormwater management measures is of great significance in facilitating the construction of sponge cities. By analyzing the relevant literature at home and abroad, this paper clarifies the relevant definition and content scope of the layout optimization of urban stormwater management measures, constructs the whole process structure including pre-preparation, model algorithm, post-evaluation and decision-making of the layout optimization of stormwater management measures, systematically analyzes relevant information of each step of layout optimization, explores current research status and gaps of each part of the framework, and puts forward suggestions for more scientific layout optimization. Layout optimization of urban stormwater management measures based on the whole process structure above is both theoretically and practically momentous for promoting the construction of sponge cities in China.